Mobile application for online recruitment system - Kiew, Xian Zheng (2022)

(untitled)
This project is a mobile application for online recruitment system as final year project in UTAR for academic purpose. It will provide students with the knowledge and experience about mobile application development along with user interface design and database design. As mobile application becoming more commonly to use by people due to it portable and mobility to access anywhere anytime, thus, this is the reason to develop an online recruitment system on mobile platform. Furthermore, the online recruitment system was designed to help job seekers to search and apply for available jobs. It will also help employers to post for jobs and recruit employees with simplified recruitment processes. The main function of this system is to allow job seekers and employers to search for available jobs more easier and post for jobs through the system. Many of the online recruitment system did not provide the job postings function for the employers to post job through the mobile application. Hence, this proposed project will provide a more convenience way of posting job function to the employers when using the mobile application. A user-friendly system will be developed for the users to increase the satisfaction users and improve the user experiences. Besides, the proposed project will implement a special function to improve the job searching processes such as 3 types of user category login features. All the job postings data will be stored in Firebase Realtime Database and the data will be retrieved to the font-end system to show a job listing to the users. The output of this project will be an Android application which will retrieve all data from database and show it in the front-end system.